Resistance to 16-Membered Macrolides, Tiamulin and Lincomycin in a Swine Isolate of Acholeplasma laidlawii - María M. Tavío; Ana S. Ramírez; Carlos Poveda; Rubén S. Rosales; Cristina F. Malla; José B. Poveda (MDPI AG, 2021)
Acholeplasma (A.) laidlawii is an opportunistic pathogen with the ability to disseminate resistance determinants to antibiotics; however, its resistance to macrolides has been less studied. The aim of the present study was to characterize the mechanisms responsible for the resistance to macrolides, tiamulin and lincomycin found in a strain of A. laidlawii isolated from a pig with pneumonia. MICs of erythromycin, 15- and 16-membered macrolides, tiamulin and lincomycin were determined by microdilution method with and without reserpine, an inhibitor of ABC efflux pumps and regions of the genome were sequenced. Reserpine only decreased lincomycin MIC but it did not change the MICs of macrolides and tiamulin. The analysis of the DNA sequence of 23S rRNA showed nucleotide substitutions at eight different positions, although none of them were at positions previously related to macrolide resistance. Five mutations were found in the L22 protein, one of them at the stop codon. In addition, two mutations were found in the amino acid sequence of L4. The combination of multiple mutations in the ribosomal proteins L22 and L4 together with substitutions in 23S rRNA DNA sequence was associated with the resistance to macrolides, the pleuromutilin and lincomycin in the studied A. laidlawii strain.